2021
DOI: 10.1590/2317-4889202120200088
|View full text |Cite
|
Sign up to set email alerts
|

Practical mineralogical quantification of bentonites supported for a PXRD calibrated hkl model

Abstract: In the bentonite industry-exploration and beneficiation-ore quality control has been traditionally carried out using the swelling parameter, denominating those that swell as naturally sodium bentonites and those that do not as naturally non-sodium bentonites. However, the properties of the bentonites can vary due to the quantity and cationic type of montmorillonite. The variation in those properties cannot always be predicted, because there is still no consolidated and convenient method for clays mineralogical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The result of the composition analysis of each phase (Weight %) is shown in the pie chart (Figure 1a). The same profile of the diffractograms was characterized by bentonite clay as demonstrated in studies [33,34]. Geologically, formed mainly from the chemical alteration of volcanic glass and pyroclastic or volcanoclastic rocks, bentonite clay rocks are composed basically of Na-montmorillonite.…”
Section: Mineralogical Analysis By X-ray Diffractionmentioning
confidence: 55%
See 1 more Smart Citation
“…The result of the composition analysis of each phase (Weight %) is shown in the pie chart (Figure 1a). The same profile of the diffractograms was characterized by bentonite clay as demonstrated in studies [33,34]. Geologically, formed mainly from the chemical alteration of volcanic glass and pyroclastic or volcanoclastic rocks, bentonite clay rocks are composed basically of Na-montmorillonite.…”
Section: Mineralogical Analysis By X-ray Diffractionmentioning
confidence: 55%
“…The result of the composition analysis of each phase (Weight %) is shown in the pie chart (Figure 1a). The same profile of the diffractograms was characterized by bentonite clay as demonstrated in studies [33,34].…”
Section: Mineralogical Analysis By X-ray Diffractionmentioning
confidence: 72%
“…From Table 6, it is identi ed that both clays mainly contained silicon oxide (SiO 2 ) and aluminum oxide (Al 2 O 3 ), dominant constituents of all clay minerals. e relatively high percentage of Fe 2 O 3 (~10%) is typical for most Brazilian bentonites [35]. e Fe 2 O 3 and TiO 2 were the main impurities (1.2-1.3%) for kaolinite.…”
Section: Characterization Of Bindersmentioning
confidence: 96%
“…High quality commercial bentonite typically consists of over 80% montmorillonite. However, this content varies significantly amongst different commercial bentonites, ranging from 60% to more than 80% [64]. During the canister deposition process, the bentonite buffer is composed of low-water-content (10-17%) bentonite blocks.…”
Section: Effect Of Bentonite Dry Density and Microbial Activity On Be...mentioning
confidence: 99%
“…Therefore, a continuous evaluation of microbial activity and diversity in such a challenging environment is essential for the safety assessments of the DGR concept. In recent years, numerous studies have investigated the behavior of allochthonous bacteria in highly compacted bentonite (Figure 1), as well as the cultivation of microbes derived from the bentonite itself [6,64,74,75]. For instance, Jalique et al [76] identified Gram-positive spore-forming bacteria in highly compacted bentonite and inferred that the formation of spores might enhance bacterial survival in the challenging conditions of this environment.…”
Section: Effect Of Bentonite Dry Density and Microbial Activity On Be...mentioning
confidence: 99%